The Role of Congregational Dhuha Prayer Habituation in Fostering Students’ Discipline and Spiritual Intelligence - Mohammad Hasyim; Umar Manshur; Mona Novita; Filda Nuriah A'yun; Nahid Ayad (GHAITSA : Islamic Education Journal, 2026)
The decline of student discipline and the limited integration of spiritual development in primary education highlight the need for holistic educational approaches, particularly in Islamic school contexts. This study investigates the role of congregational Dhuha prayer habituation in fostering students’ discipline and spiritual intelligence in an Islamic elementary school. A qualitative case study design was employed, involving one principal, two teachers, and eleven sixth-grade students selected purposively based on their direct and sustained participation in the program. Data were collected through semi-structured interviews and documentary analysis, and analyzed using the interactive qualitative model of Miles, Huberman, and Saldaña. The findings indicate that the congregational Dhuha prayer program functioned as a structured institutional routine that supported punctuality, procedural readiness, behavioral responsibility, emotional calmness, intrinsic religious motivation, and growing spiritual competence. Students’ repeated participation in communal worship fostered both observable disciplinary behaviors and internal spiritual development within a supportive educational environment. This study contributes a co-emergence perspective, demonstrating that discipline and spiritual intelligence may develop simultaneously through a single embodied religious practice rather than as separate educational outcomes. The findings suggest that structured spiritual habituation may serve as a meaningful pedagogical strategy for holistic character formation in Islamic primary education